Curcumin induces human HT-29 colon adenocarcinoma cell apoptosis by activating p53 and regulating apoptosis-related protein expression - Song,G. (2005)
Curcumin, a major yellow pigment and active component of turmeric, has multiple anti-cancer properties. However, its molecular targets and mechanisms of action on human colon adenocarcinoma cells are unknown. In the present study, we examined the effects of curcumin on the proliferation of human colon adenocarcinoma HT-29 cells by the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide method and confirmed the curcumin-induced apoptosis by morphology and DNA ladder formation. At the same time, p53, phospho-p53 (Ser15), and other apoptosis-related proteins such as Bax, Bcl-2, Bcl-xL, pro-caspase-3, and pro-caspase-9 were determined by Western blot analysis. The colon adenocarcinoma cells were treated with curcumin (0-75 µM) for 0-24 h. We observed that p53 was highly expressed in HT-29 cells and curcumin could up-regulate the serine phosphorylation of p53 in a time- and concentration-dependent manner. An increase in expression of the pro-apoptotic factor Bax and a decrease in expression of the anti-apoptotic factor Bcl-2 were also observed in a time-dependent manner after exposure of 50 µM curcumin, while the expression of the anti-apoptotic factor Bcl-xL was unchanged. Curcumin could also down-regulate the expression of pro-caspase-3 and pro-caspase-9 in a time-dependent manner. These data suggest a possible underlying molecular mechanism whereby curcumin could induce the apoptosis signaling pathway in human HT-29 colon adenocarcinoma cells by p53 activation and by the regulation of apoptosis-related proteins. This property of curcumin suggests that it could have a possible therapeutic potential in colon adenocarcinoma patients.